Hepatocellular carcinoma in a North American population: Does hepatobiliary MR imaging with Gd‐EOB‐DTPA improve sensitivity and confidence for diagnosis?. Issue 2 (25th September 2012) - Bashir, Mustafa R.; Gupta, Rajan T.; Davenport, Matthew S.; Allen, Brian C.; Jaffe, Tracy A.; Ho, Lisa M.; Boll, Daniel T.; Merkle, Elmar M.
Abstract Purpose: To evaluate the value of hepatobiliary phase imaging for detection and characterization of hepatocellular carcinoma (HCC) in liver MRI with Gd‐EOB‐DTPA, in a North American population. Materials and Methods: One hundred MRI examinations performed with the intravenous injection of Gd‐EOB‐DTPA in patients with cirrhosis were reviewed retrospectively. Nodules were classified as HCC (n = 70), indeterminate (n = 33), or benign (n = 22). Five readers independently reviewed each examination with and without hepatobiliary phase images (HBP). Lesion conspicuity scores were compared between the two readings. Lesion detection, confidence scores, and receiver operating characteristic (ROC) analysis were compared. Results: Lesion detection was slightly improved for all lesion types with the inclusion of the HBP, and was substantially higher for small HCCs (96.0% versus 85.3%). Mean confidence scores for the diagnosis of HCC increased for HCCs overall and each size category (P < 0.001). Diagnostic performance improved with the addition of the HBP (aggregate AROC 87.7% versus 80.0%, P < 0.01), and sensitivity for characterization improved (90.9% versus 78.3%, P < 0.01) while specificity was unchanged. Conclusion: Hepatobiliary phase imaging may improve small lesion detection (<1 cm) and characterization of lesions in general, in MRI of the cirrhotic liver with Gd‐EOB‐DTPA. J. Magn. Reson. Imaging 2013;37:398–406. © 2012 Wiley Periodicals, Inc.